Prognostic Value of Total Bilirubin in Patients With ST-Segment Elevation Acute Myocardial Infarction Undergoing Primary Coronary Intervention - Zhao, Xiaoxiao; Wang, Ying; Liu, Chen; Zhou, Peng; Sheng, Zhaoxue; Li, Jiannan; Zhou, Jinying; Chen, Runzhen; Chen, Yi; Zhao, Hanjun; Yan, Hongbing (Frontiers in Cardiovascular Medicine, 2020)
Background: Bilirubin, a natural product of heme catabolism, has antioxidant and anti-inflammatory activities and is inversely associated with stable coronary artery disease. However, the relationship between the bilirubin levels and long-term outcomes in patients with ST-segment elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (PPCI) remains unknown. This study aimed to establish a score model based on bilirubin for predicting major adverse cardiovascular events (MACEs) and stratify patients to the level of care. Methods and Results: Data of 4,151 consecutive patients with STEMI who underwent PPCI were evaluated, and 3,708 cases were analyzed. The total bilirubin (TBil) levels were measured during admission, and the study population was divided into two groups. The high TBil group (n = 143) comprised patients who had a TBil level of ≥22 μmmol/L, and the low TBil group (n = 3,565) comprised patients who had a TBil level of <22 μmmol/L. The median follow-up period was 754 days (2.066 years). The MACE was significantly lower in the high TBil group than in the low TBil group (3.5% vs. 11.0%, p = 0.001). In the multivariate Cox regression analysis, a significant association was noted between the TBil levels and adjusted risk of MACE (hazard ratio, 0.279; 95% confidence interval, 0.088–0.877; p = 0.029). A prediction score model composed of TBil, age, hypertension history, and other eight variables was developed, with scores ranging from 0 to 500. The scores categorized patients into low-, medium-, and high-risk categories. The cumulative survival rate was significantly higher in the low-risk group than in the medium- and high-risk groups for MACE, all-cause death, cardiac death, recurrent myocardial infarction, and ischemic stroke (p < 0.001, p < 0.001, p < 0.001, p = 0.030, and p = 0.001, respectively). The area under the curve of the TBil score was 0.768; this was significantly greater in the pairwise comparison with the Global Registry of Acute Coronary Events score (p = 0.0012). Conclusion: The new prediction score model based on TBil could be used in clinical practice to support risk stratification as recommended in the clinical guidelines.